How is the role of dental health cadres during the Covid-19 pandemic? - Patient referrals and counseling - Suharja, Eliati Sri; Wahyuni, Yun; Nugroho, Cahyo (Journal of Drug Delivery and Therapeutics, 2022)
Background: Health cadres are volunteers, recruited from, by, for the community. There are two kinds of cadres can play a role in the health sector, namely in the Posyandu (Integrated Healthcare Center). Objective: to determine the relationship between cadres' participation in counseling and referral of dental and oral patients with a visit to the dental polyclinic during the Covid-19 period at the Banjar Health Center 1. Method: analytical descriptive with a cross sectional design. Sample determination of 40 cadres with purposive sampling technique. Results: showed that the level of ability of cadres in dental and oral health counseling efforts with the number of visits to the dental polyclinic at Banjar 1 Health Center for a period of 2 months showed p=0.011, as well as for the measurement of dental patient referrals with visits, p= 0.011. Conclusion: there is a relationship between the participation of cadres in counseling and referral of dental and oral patients with visits to the dental polyclinic during the Covid-19 period at the Banjar 1 Health Center with statistical results p=0.011Keywords: Role of cadres, counseling, patient referrals.